Rancang Bangun Aplikasi “SICATAT“ Sistem Pencatatan Barang Habis Pakai Berbasis Web Menggunakan Laravel - Gunawan, Aldi Rizky; Rini, Eka Mistiko; Suwardiyanto, Devit (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
An educational institution has a unit responsible for managing consumable goods. Currently, this process is still conducted semi-computerized or manually using manual formulas and online spreadsheets. This leads to inefficiencies and inaccuracies in grouping and numbering used and new incoming items. This research aims to address these issues by developing a web-based application called